PENGEMBANGAN SIKAP SPIRITUAL ISLAMI DAN KETRAMPILAN PROSES SAINS SISWA DALAM PEMBELAJARAN IPA DI MADRASAH IBTIDAIYAH KRUENG SABEE ACEH JAYA - Wati Oviana (Jurnal Ilmiah Didaktika, 2016)
One of the aims in learning natural science is to lead the students have a strong belief of a greatness of God and also to develop their skill of natural science. For that reason, in natural science teaching-learning process, a teacher has to develop students’ spiritual attitude and process skill in order to reach curriculum demand. This study aims to have information about teachers’ ability in developing students’ Islamic spiritual attitude and process skill based on their lesson planning and learning process of natural science classroom at Madrasah Ibtidaiyah Krueng Sabee. The research method used was descriptive method. The instrument of the research was an analysis guide of RPP to find the ability of teacher in developing spiritual attitude and natural science process skill in RPP; a learning observation sheet to find the ability of the teachers in developing spiritual attitude and natural science process skill in learning process; and an interview guide to find the teachers’ obstacles in developing spiritual attitude and natural science process skill as a support data. The data was analyzed by using percentage which later was described based on the research questions. The study found that the teachers’ ability in developing spiritual attitude was still very low with percentage 0%; meanwhile, the ability of teachers in developing spiritual attitude in learning process was variety for each activity; Only at the beginning activities, the teachers were able to develop spiritual attitude with percentage 100%; for final activities, the result was 50% and for core activities was 0%. The teachers’ ability of sainsprocessskill was also not good as not all the teachers were able to develop a complete KPS indicator in both RPP and learning process.